KEPEMIMPINAN TRANSFORMASIONAL SEBAGAI STRATEGI PENGEMBANGAN BUDAYA ORGANISASI DAN KOMPETENSI PEDAGOGIK DI SMP XYZ - Iriani, Everista (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the role of transformational leadership in shaping organizational culture and enhancing pedagogical competence at XYZ Junior High School. Using a case study approach, data were collected through semi-structured interviews, observations, and document analysis involving the principal, vice principal, pedagogical leaders, and teachers. The findings reveal that transformational leadership supports the strengthening of organizational culture through motivation, a shared vision, and an inclusive learning community. However, implementation faces challenges within the four dimensions of transformational leadership: Idealized Influence, Intellectual Stimulation, Individualized Consideration, and Inspirational Motivation. Organizational culture-related challenges include communication across hierarchical levels, aligning leadership practices, and addressing diverse needs and aspirations. Organizational culture plays a crucial role in preparing teachers for change, fostering collaboration, creating a positive work environment, and supporting continuous professional development. This study emphasizes the importance of integrating transformational leadership with a responsive organizational culture to navigate curriculum changes and strengthen pedagogical competence. Keywords: transformational leadership, organizational culture, pedagogical competence